Surface modification of silica-based marine sponge bioceramics induce hydroxyapatite formation - Barros, Alexandre A. (2014)
Marine biomaterials are a new emerging area of research with significant applications. Recently, researchers are dedicating considerable attention to marine-sponge biomaterials for various applications. We have focused on the potential of biosilica from Petrosia ficidormis for novel biomedical/industrial applications. A bioceramic structure from this sponge was obtained after calcination at 750ºC for 6 hours in a furnace. The morphological characteristics of the 3D architecture were evaluated by scanning electron microscopy (SEM) and micro-computed tomography revealing a highly porous and interconnected structure. The skeleton of Petrosia ficidormis is a siliceous matrix composed of SiO2, which does not present inherent bioactivity. Induction of bioactivity was attained by subjecting the bioceramics structure to an alkaline treatment (KOH 2M) and acidic treatment (HCl 2M) for 1 and 3 hours. In vitro bioactivity of the bioceramics structure was evaluated in simulated body fluid (SBF), after 7 and 14 days. Observation of the structures by SEM, coupled with spectroscopic elemental analysis (EDS), has shown that the surface morphology presented a calcium-phosphate CaP coating, similar to hydroxyapatite (HA). The determination of the Ca/P ratio, together with the evaluation of the characteristic peaks of HA by infra-red spectroscopy and X-ray diffraction, have proven the existence of HA. In vitro biological performance of the structures was evaluated using an osteoblast cell line andthe acidic treatment has shown to be the most effective treatment. Cells were seeded on the bioceramics structures and their morphology, viability and growth was evaluated by SEM, MTS assay and DNA quantification, respectively, demonstrating that cells are able to grow and colonize the bioceramic structures.